Pengaruh Motivasi Kerja, Kepemimpinan Kepala Sekolah dan Iklim Kerja Terhadap Kinerja Guru di Sekolah Kecamatan Tana Lia Kabupaten Tana Tidung - Wahit, Abdul; Purwanto, Nurtanio Agus; Robi, La (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of work motivation, school principal leadership, and work climate on teacher performance in schools in Tana Lia District, Tana Tidung Regency. The background of this study is the low motivation and unfavorable work climate, which have the potential to hinder teacher performance. Using a quantitative approach with an ex post facto method, the study population included 56 teachers, selected as a sample through total sampling. The instrument used was a closed-ended questionnaire, and the data were analyzed using independent t-tests and simple linear regression. The results of the study indicate that, partially, work motivation, school leadership, and work environment significantly influence teacher performance, with respective contributions of 50.2%, 10.1%, and 6.8%. Simultaneously, these three variables also have a significant influence with a total contribution of 53.2%. The conclusion of this study emphasizes the importance of these factors in improving teacher performance. The implications of these findings can serve as a basis for educational policies aimed at enhancing human resource quality in Tana Tidung Regency.